SISTEM INFORMASI MOBILE ASSISTANT MAHASISWA JURUSAN SISTEM INFORMASI FAKULTAS KOMPUTER UNIVERSITAS POTENSI UTAMA BERBASIS ANDROID: Array (Universitas Harapan Medan, 2019)
It has become a habit if students are still often not on time to attend lecture activities, in addition students also often forget to do assignments or prepare to face exams. This has an impact on the achievement of the values obtained not being maximized. In this study, researchers built a mobile Information System on Android-based smartphones as a reminder for students of the Faculty of Information Systems Department of the University's PotensiUtama. This application consists of two parts, namely Web-based for admin and Android-based for users who are connected using Web Service. This application is made in order to support and maximize lecture activities. This application is as a reminder alarm for students so that they always remember the lecture schedule, task collection schedule, and schedule of exam implementation. This Information System is also tested to get the desired results using the Black-Box Equivalence Partitioning testing method. The results of the Black-Box Equivalence Partitioning test show the system can run as expected.